Enhancing Students’ Self-Esteem through Psychodrama with Hand Puppets: A Study in Islamic Schools - Ulvina Rachmawati; Nafisah Ainur Rohmah; Danneth Krystel A. Sia (Pamomong: Journal of Islamic Educational Counseling, 2025)
This study was motivated by the high academic and social demands experienced by students in faith-based schools, which can contribute to low self-esteem. These differentiated demands prompt students to compare themselves with peers in public schools and to evaluate their abilities, physical conditions, and economic status negatively, leading to feelings of inferiority in social interactions and academic performance. This pre-experimental study with a one-group pretest and posttest design examined the effectiveness of a psychodrama hand-puppet intervention in enhancing students’ self-esteem. A purposive sampling technique was used to select 10 students from MA Sirojul Hikmah who had the lowest self-esteem scores based on a self-esteem scale adapted to local cultural values and Islamic principles (Cronbach’s α = .816; item–total correlations > .30). Data were analyzed using the Wilcoxon signed-rank test. The results showed a 77.6% improvement in self-esteem, with the mean score increasing from 76 prior to the intervention to 135 afterward. The Wilcoxon test indicated that the psychodrama hand-puppet intervention was effective in increasing students’ self-esteem (p = .005). Psychodrama also significantly improved the dimensions of significance (p = .005), competence (p = .005), power (p = .005), and virtue (p = .005). These findings offer practical implications for Islamic schools (madrasah and pesantren) by providing an alternative intervention to foster more positive self-esteem among students. Future research should consider larger sample sizes, alternative research designs, and variation in gender and coping strategies to obtain more comprehensive results.